Water quality deterioration: A study of household drinking water quality in rural Honduras - Trevett, Andrew F.; Carter, Richard C.; Tyrrel, Sean F. (Taylor and Francis, 2004)
There is growing awareness that drinking-water can become contaminated following its collection from communal sources such as wells and tap-stands, as well as during its storage in the home. This study evaluated the post-supply drinking-water quality in three rural Honduran communities using either a protected hand-dug well or borehole supply. Water management practices were documented as a basis for further research to improve household drinking-water quality. Membrane filtration was used to compare thermotolerant coliform levels in samples taken from community wells and household drinking-water storage containers. Over a 2-year period, water quality was examined in 43 households and detailed observation made of typical collection, storage and usage practice. Substantial water quality deterioration occurred between the points of supply and consumption. Deterioration occurred regularly and frequently, and was experienced by the majority of study households. Only source water quality appeared to be a significant factor in determining household water quality. None of the storage factors examined, i.e. covering the container, type of container, the material from which the container was made, and hours stored, made any significant difference to the stored water quality. Observation of household water management shows that there are multiple points during the collection to use sequence where pollution could occur. The commonality of water management practice would be an asset in introducing appropriate intervention measures.
Keywords: Deterioration; Honduras; household; hygiene; storage; water quality